Hubungan Usia, Paritas Dan Riwayat Abortus Dengan Kejadian Abortus Pada Ibu Hamil Di Rumah Sakit Ibu Dan Anak Bunda Jakarta Tahun 2021 - 2022 - Yutra Rinawati; Nirmala Harahap; Agnomelsya Bangaran (Indonesian Journal of Midwifery Scientific, 2024)
It is estimated that 20-25% of all pregnant women will have symptoms of bleeding or threat of abortion in the first trimester and 50% will end in abortion. More than 80% occur at a gestational age of less than 14 weeks. To determine the relationship between age, parity and history of abortion with the incidence of abortion in pregnant women at the Jakarta Mother and Child Hospital which occurred in the period 2021 to 2022. The type of research used is quantitative analysis with the research design used is a retrospective cohort with a cross-sectional approach sectional. The research population was pregnant women who visited RSIA Bunda Jakarta for the period 2021, totaling 6,425 people and 2022, totaling 5,772 people. The results of the chi-square test showed a relationship between the research variables obtained by age with a p-value of 0.001 (p <0.05), parity with a p-value of 0.428 (p >0.05), and history of abortion p-value of 0.009 (p < 0.05). Accompanied by the OR results for each variable, age OR 2.405 CI=1.026-5.640, parity OR 1.400 CI= 0.608-3.223 and history of abortion OR 3.368 CI=1.333-8.512. There is a relationship between age and history of abortion and the incidence of abortion and there is no relationship between parity and the incidence of abortion in pregnant women. For this reason, it can be an input in policy planning and find the best way to prevent, handle and minimize the number of pregnant women who experience abortions.